Quantification of Enzymatic Antioxidants and Level of Lipid Peroxidation in Pantja Buck Seminal Plasma at Different Stages of Semen Freezing - Kumar, Sunil; Ambwani, Tanuj Kumar; Prasad, Shiv; Gupta, Harihar Prasad; Tewari, Anuj (The Indian Journal of Animal Reproduction, 2025)
Present study was conducted to quantify the status of enzymatic antioxidants and level of lipid per-oxidation in Pantja buck seminal plasma at different stages of semen freezing. Thirty- two (32) ejaculates were collected from four (04) sexually mature Pantja bucks using artificial vagina method during breeding season. In order to eliminate the individual differences among bucks, the satisfactory semen ejaculates after initial examination were mixed in a pool (4 ejaculate = 1 pooled sample) to form eight pooled samples. All pooled samples were diluted in glycerinated egg yolk tris extender to obtain a final concentration of 240 million spermatozoa/ml. Thereafter, these samples were evaluated for the status of antioxidative enzymes (superoxide dismutase, catalase, glutathione peroxidase and glutathione reductase) in relation to lipid peroxidation (malondialdehyde estimation) of sperm plasma membrane at different stages (neat, post-dilution, post-equilibration and post-thaw) of semen freezing. The overall mean values of natural enzymatic antioxidants viz; su peroxide dismutase, catalase, glutathione peroxidase and glutathione reductase and malondialdehyde in the neat seminal plasma of eight pooled samples were 296.73±6.17 U/ml, 1.63±0.06 U/ml, 10.45±0.37 nmol/ml, 61.74±1.9 nmol/ml and 2.19±0.06 nmol/ml respectively. The mean values of above enzymes continuously decreased significantly (P< 0.05) in post-thawed semen samples and were 232.76±9.78 U/ml, 0.64±0.03 U/ml, 3.05±0.16 nmol/ml and 31.84±1.9 nmol/ml, respectively, while the mean value of malondialdehyde (8.02±0.10 nmol/ml) increased significantly indicating varying levels of oxidative stress during semen freezing. The findings of the present study conclude that maintaining a robust antioxidant defense in semen during the freezing and thawing process is essential for achieving optimal post-thaw semen quality